Novel lifetime routing metric for IEEE 802.11 wireless mesh networks. (2018) - Azhari, Seyed Vahid; Afshari, Niloofar; Nassiri, Mohammad
We propose least critical lifetime routing (LCLR) for improving the lifetime of battery operated 802.11 wireless mesh networks. Our protocol uses a novel expected lifetime metric to identify the critical node in a path and adjusts the amount of traffic over that path accordingly. We also adopt a simple route congestion measure to further fine tune the amount of traffic sent over a given path. More importantly, LCLR also takes interference and congestion into account. Moreover, we use a simple path available bandwidth estimation approach, which is integrated into the routing process. We evaluate the performance of LCLR by using NS2 simulations and compare it to that of ad hoc on-demand distance vector (AODV), minimum total energy routing and the optimal solution to the maximum lifetime routing problem. Our results obtained for different network topologies suggest that LCLR performs close to the optimum.